OLCBot: Dissemination Of Interactive Information Related To Indonesia's Omnibus Law With The Implementation of Fuzzy String Matching Algorithm and Sastrawi Stemmer - Amalia, Amalia; Lidya, Maya Sylvi; Andrian, Andrian; Zamzami, Elviawaty Muisa; Hardi, Sri Melvani (2022 6th International Conference on Electrical, Telecommunication and Computer Engineering (ELTICOM), 2022)
Omnibus Law is a concept of the primary law that regulates as well as revises several laws. Undang Undang Cipta Kerja (in English: Job Creation Law), which is now ratified as Law of the Republic of Indonesia No. 11 of 2020 on Job Creation, is one of the targets of the omnibus law. However, since it was ratified on Monday, October 5^{th}, 2020, the law has continued to cause debate and polemic from various elements of society. The reason is the lack of information media related to the Job Creation Law, especially interactive media for information dissemination. Moreover, the official document has 1187 pages which led the people hard to comprehend the document itself. One of the technologies that can be used as interactive media is a chatbot. A chatbot is a computer program that can simulate a conversation with a human. Chatbot itself is the development of Natural Language Processing. This study aims to build OLCBot, a chatbot that can act as an interactive medium for disseminating information on this law. Using the Fuzzy String Matching approach and Sastrawi stemmer, this chatbot is expected to understand and answer users' questions related to the law. The chatbot knowledge base was taken from the manuscript of the Law of the Republic of Indonesia No. 11 of 2020 on Job Creation. The results showed that OLCBot had an accuracy rate of 91.30% in answering questions from users regarding the Job Creation Law or the chatbot was able to answer 42 out of 46 questions.